Clement Comer Clay, Digest of the Laws of Alabama: Containing all the Statutes of a Public and General Nature, in Force at the Close of the Session of The General Assembly, in February, 1843. To Which are Prefixed, the Declaration of Independence; the Constitution of the United States; the Act to Enable the People of Alabama to Form a Constitution and State Government, &c.; and the Constitution of the State of Alabama Page 413 § 8 - (:unkn) unknown (General Publisher, 1843)
Prohibited fighting or discharging a firearm or air-gun in any city, town, or miltiia muster, or public assembly. Violators fined not less than one hundred nor more than five hundred dollars, or imprisoned not exceeding six months, or both at the discretion of the judge.
--
Keywords: DUELING